A Collection of all the Public Acts of Assembly, of the Province of North-Carolina 215 (1752) - (:unkn) unknown (My University, 1746)
"the Militia of this Government shall consist of all the Freemen and Servants... between the Age of Sixteen Years, and Sixty?" Further, the statute required every member of the militia to be "well provided with a gun, fit for service, a Cartouch Box, and a Sword, Cutlass, or Hanger, at least 12 charges of powder and ball, or swung shot, and six spare flints?"
Keywords: REQUIRED POSSESSION